Rumen metabolites in crossbred calves fed graded levels of rumen degradable protein and undegraded dietary protein - CHATURVEDI, O H; WALLI, T K (The Indian Journal of Animal Sciences, 2014)
Crossbred calves (4) each fitted with a rumen cannula, were fed on 4 types of concentrates, varying in CP (%) and also the RDP: UDPratio, viz. 23,4 and 79: 21 foy,T1,21.0 and 68: 32 for T2, 18.4 and 59: 41 for and 15.9 and 48: 52 for T4 groups along with wheat straw ad lib. and green maize @ 0.5 kg/I 00 kg body weight, in a 4 x 41alin square design to study the rumen metabolites, Calves in Tl, T2, T3 and T4 were fed CP, respectively, 20% higher, normal, 10 and 20% lesser than the recommendations, After 21 days duri'ng each switch over, the rumen liquor samples from each animal were drawn at 0, 2,4,6 and 8 hr offceding and pH, TYFA, individual VFA, total N, NH, N, urea N and non ammonia nitrogen (NAN) were assessed. The variation in pH and TYFA because of hours of feeding and treatments was significant. The ruminal pH decreased over the period of sampling from 0 to 8 hr of feeding, except in T4 whete the minimum value was seen at 6 hr. The TYFA concentration showed a significant decreasing trend by decreasing the CP and RDP content and incteasing the UDP content in the diet. Similarly, the molar concentration of individual YFAs (acetate, propionate and butyrate) also decreased from T1 to T4 as the UDP content increased in that order. However, the A/P ratio progressively increased (P